Impaired Fas-Fas Ligand Interactions Result in Greater Recurrent Herpetic Stromal Keratitis in Mice. (4th October 2015) - Yin, Xiao-Tang; Keadle, Tammie L.; Hard, Jessicah; Herndon, John; Potter, Chloe A.; Del Rosso, Chelsea R.; Ferguson, Thomas A.; Stuart, Patrick M.
Abstract : Herpes simplex virus-1 (HSV-1) infection of the cornea leads to a potentially blinding condition termed herpetic stromal keratitis (HSK). Clinical studies have indicated that disease is primarily associated with recurrent HSK following reactivation of a latent viral infection of the trigeminal ganglia. One of the key factors that limit inflammation of the cornea is the expression of Fas ligand (FasL). We demonstrate that infection of the cornea with HSV-1 results in increased functional expression of FasL and that mice expressing mutations in Fas ( lpr ) and FasL ( gld ) display increased recurrent HSK following reactivation compared to wild-type mice. Furthermore, both gld and lpr mice took longer to clear their corneas of infectious virus and the reactivation rate for these strains was significantly greater than that seen with wild-type mice. Collectively, these findings indicate that the interaction of Fas with FasL in the cornea restricts the development of recurrent HSK.